Evaluation of acute and subchronic oral toxicity of S-Men in experimental Wistar rats - Tung, Tran Thanh; Dung, Nguyen Chi; Tri, Nguyen Thanh (Tạp chí Nghiên cứu Y học, 2026)
This study aimed to assess the acute and repeated-dose oral toxicity of the S-Men formulation in experimental animals. Acute toxicity was evaluated in Wistar rats via oral administration following the OECD 423 fixed-dose method. Subchronic toxicity was investigated through a 90-day repeated-dose oral study per OECD 408 guidelines. The acute toxicity results demonstrated that S-Men at doses up to 5000 mg/kg did not cause acute toxicity, and the LD50 could not be determined. In the repeated-dose study, S-Men administered at 1096 mg/kg/day and 3288 mg/kg/day for 90 consecutive days caused no significant change in general condition, body weight, hematological and biochemical parameters, or liver and kidney histopathology compared to the normal control group. Thus, S-Men exhibited no acute toxicity at doses up to 5000 mg/kg and did not cause subchronic toxicity at 1096 and 3288 mg/kg/day over 12 weeks in Wistar rats.